Thiamet G effects on mitochondria and AD pathological hallmarks in human iPSC derived models. (December 2021) - Wilkins, Heather M; Lysaker, Colton R; Messer, Taylor B; Alghusen, Ibtihal; Troutwine, Benjamin M; Swerdlow, Russell H; Slawson, Chad M
Abstract: Background: Thiamet‐G (TMG) has recently been examined in human Alzheimer's Disease (AD) clinical trials. TMG increases total O‐GlcNAc levels through inhibition of O‐GlcNAcase (OGA). Modulation of OGA through genetic (overexpression or knockdown) or chemical means (TMG) has shown positive effects in transgenic AD animal models. Here, we sought to examine the effects of TMG and increased O‐GlcNAc levels on induced pluripotent stem cell (iPSC) models of AD using both neurons and cerebral organoids. Method: Human iPSCs were derived from the KU ADC fibroblast repository or obtained from WiCell. Twelve age and sex matched iPSC lines were used (6 non‐demented/ND, 2 familial AD/FAD with APP V717I mutation, and 4 sporadic AD/SAD). Neurons or cerebral organoids were derived and matured from iPSCs using StemCell Technologies StemDiff protocols and reagents. iPSC derived neurons (iNeurons) and cerebral organoids were treated with 20 µM or 40 µM TMG for 14 days. Cell culture supernatants were collected and Aβ/sAPP measured. Protein lysates were used to measure O‐GlcNAc, mitochondrial proteins, tau, and cell signaling proteins. Seahorse Bioanalyzer was used to measure oxygen consumption rates and fluorescent imaging for mitochondrial membrane potential, mitochondrial superoxide, and mitochondrial number/turnover. Result: ND and SAD iNeurons treated with TMG had lower Aβ40 . SAD iNeurons had reduced Aβ42 with TMG treatment. PHF1 tau and total tau were increased in TMG treated SAD iNeurons. TMG treatment in ND and SAD iNeurons increased mitochondrial membrane potential and mitochondrial superoxide. TMG treatment increased mitochondrial mass for both new and old mitochondria in SAD iNeurons. In cerebral organoids, TMG treatment increased Aβ40 in ND and SAD samples, increased Aβ42 in SAD samples, and increased the ratio of Aβ42 / Aβ40 in ND and SAD samples. Overall, no changes were observed in FAD TMG treated iNeurons or cerebral organoids. Conclusion: Modulation of O‐GlcNAc robustly effects AD pathological hallmarks and mitochondrial function in SAD but not FAD derived iNeurons and cerebral organoids. Further study is warranted to understand the mechanisms and lack of effect in FAD derived cell and organoid models.